2016
DOI: 10.1016/j.brainresbull.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to nicotine increases nicotinic acetylcholine receptor density in the reward pathway and binge ethanol consumption in C57BL/6J adolescent female mice

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 84 publications
4
22
0
Order By: Relevance
“…Brief pretreatment of male rats during early adolescence (P28–31) with low doses of nicotine enhances subsequent acquisition of alcohol self-administration (21). Periadolescent nicotine (P35–44) also enhances ethanol consumption in female mice (134), although one study reported no effect of adolescent nicotine exposure in rats on ethanol intake in adulthood (135). The discrepancy may be due to different age of testing for ethanol consumption or continuous versus intermittent exposure paradigms.…”
Section: Concurrent Use Of Nicotine and Alcoholmentioning
confidence: 99%
“…Brief pretreatment of male rats during early adolescence (P28–31) with low doses of nicotine enhances subsequent acquisition of alcohol self-administration (21). Periadolescent nicotine (P35–44) also enhances ethanol consumption in female mice (134), although one study reported no effect of adolescent nicotine exposure in rats on ethanol intake in adulthood (135). The discrepancy may be due to different age of testing for ethanol consumption or continuous versus intermittent exposure paradigms.…”
Section: Concurrent Use Of Nicotine and Alcoholmentioning
confidence: 99%
“…In contrast, [23] observed that female adolescent mice (PND 35-41) exposed to nicotine showed increased bottle-drinking ethanol consumption on (PND [41][42][43][44]. The effects of nicotine exposure during adolescence on ethanol intake seem to depend on the treatment age, duration, strain, sex, and nicotine withdrawal period [23,40]. To our knowledge, this is the first study that has demonstrated increased operant saccharine self-administration while assessing the consequences of nicotine pretreatment during adolescence in later life.…”
Section: Discussionmentioning
confidence: 90%
“…In the same way, Smith et al [39] showed that chronic continuous exposure to nicotine during adolescence (PND 35-53) did not modify ethanol intake in adulthood (PND 54-75). In contrast, [23] observed that female adolescent mice (PND 35-41) exposed to nicotine showed increased bottle-drinking ethanol consumption on (PND [41][42][43][44]. The effects of nicotine exposure during adolescence on ethanol intake seem to depend on the treatment age, duration, strain, sex, and nicotine withdrawal period [23,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescence clearly is one of the critical periods during which exposure to drug can exert life-long changes in brain and behavior. Locker et al [in this issue] show that nicotine exposure during adolescence impacts later ethanol intake in mice and the binding of nicotinic cholinergic receptors in brain. Of course, until recently, humans were rarely exposed to nicotine in the absence of numerous toxicants.…”
Section: Papers In This Mini-issue: Risk Factors For Addictionmentioning
confidence: 93%